Chromosomal Heteromorphism with Reference to Cancer and Reproduction in Human: An Appraisal - Shah, Nidhi P.; Shah, Parth S.; Dominic, Jeanny; Shah, Bhavini S.; Shah, Sandip S.; Rao, Mandava V. (International Journal of Innovative Research in Medical Science, 2019)
Background and Objectives: Human cell nucleus has, the genome consisting of euchromatin and heterochromatin. The euchromatin has gene-rich and actively functional. The heterochromatin has two components namely constitutive and facultative, where the former is highly polymorphic. It is related to numerous diseases like cancer and infertility which is now well known, though it was earlier thought to be inactive; hence the implication of these polymorphic variants of chromosomes is reviewed with respect to acrocentric and non- acrocentric types. Methodologies: The polymorphic variants can be detected by C, G, Q and R banding techniques. We usually follow G band preparation of karyotypes following World Health Organisation (WHO) manuals and their role in cancer and reproduction is reviewed. Review and Conclusion: It is emphasized that most of the p and q arms of 1, 9, 16, D and G groups and X, Y chromosomes exhibited polymorphism which are related to cancerous and infertile conditions in both sexes. Data on few non-acrocentric chromosomes like 2, 4, 8, 10, 12, 18, 19 and 20 are not available. Our review however indicated that the evaluation of specific heteromorphic variants needs to be detected using specific probes for confirmation of anomaly to assist affected cases, though earlier data indicated ambiguous information with few cases analyzed regarding assisted reproductive technologies and malignancy condition. This appraisal thus would play a key role in human chromosomal heteromorphic abnormalities and recommend genetic tests and counseling ultimately made available to the affected cases.